2008
DOI: 10.1021/ic801202d
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Heme Fe−N-Terminal Amino Group Coordination Bond in Denatured Cytochrome c

Abstract: In the denatured states of Hydrogenobacter thermophilus cytochrome c(552) (HT) and Pseudomonas aeruginosa cytochrome c(551) (PA), and their mutants, the N-terminal amino group of the polypeptide chain is coordinated to heme Fe in place of the axial Met, the His-N(term) form being formed. The coordination of the N-terminal amino group to heme Fe leads to loop formation by the N-terminal stretch preceding the first Cys residue bound to the heme, and the N-terminal stretches of HT and PA are different from each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 66 publications
3
16
1
Order By: Relevance
“…We next compared the heme electronic structures of the oxidized forms of the His−N term forms of the mutant proteins with that of the wild-type HT through analysis of their 1 H NMR spectra (Figure ). As has been demonstrated previously, the heme methyl proton signals of the His−N term form of the protein, observed in 15−40 ppm, were slightly affected by the replacement of the N-terminal amino acid residue . In addition, the signals emerging in the shift range characteristic of the HS ferriheme species, , that is, downfield of 50 ppm, were observed for the all denatured proteins at p 2 H 7.0, and their intensities varied among the proteins (see Supporting Information).…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…We next compared the heme electronic structures of the oxidized forms of the His−N term forms of the mutant proteins with that of the wild-type HT through analysis of their 1 H NMR spectra (Figure ). As has been demonstrated previously, the heme methyl proton signals of the His−N term form of the protein, observed in 15−40 ppm, were slightly affected by the replacement of the N-terminal amino acid residue . In addition, the signals emerging in the shift range characteristic of the HS ferriheme species, , that is, downfield of 50 ppm, were observed for the all denatured proteins at p 2 H 7.0, and their intensities varied among the proteins (see Supporting Information).…”
Section: Resultssupporting
confidence: 67%
“…In the 1 H NMR spectra of the oxidized cyts c , the resolved heme methyl and Fe-bound Met proton signals, which are highly sensitive to the heme active site structure, were essentially unaltered by the amino acid replacements (see Supporting Information). These results indicated that, as in the cases of the mutant proteins previously studied, the heme active site structure is not affected by the replacement of the N-terminal amino acid residue …”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations